Economic implications of foreign exchange rationing in Ethiopia - Dorosh, Paul A.; Robinson, Sherman; Ahmed, Hashim A. (International Food Policy Research Institute, 2009)
Ethiopia enjoyed remarkable economic growth from 2004/05 to 2008/09, in large part due to increases in foreign transfers and capital inflows combined with expanded domestic credit to fund major increases in private and public investments in infrastructure and housing. However, this rapid growth was accompanied by a major appreciation of the real exchange rate (by 34 percent between July 2004 and July 2008) that reduced incentives for domestic production of exportables and non-protected importables. Moreover, major external shocks to the economy (including increases in world prices of fuel in 2007 and early 2008) exacerbated foreign exchange and macro-economic imbalances. Beginning in March 2008, access to foreign exchange for imports has been restricted (rationed) to avoid excessive drawdown of foreign exchange reserves. Computable General Equilibrium (CGE) model simulations suggest that there are substantial adverse efficiency and distributional effects of foreign exchange rationing. Foreign exchange controls result in the creation of large rents that likely accrue mainly to nonpoor households. At the same time, foreign exchange controls reduce economic efficiency so that real incomes from factors of production (land, capital and labor) decline, as do overall household incomes (except for those who gain large rents). Moreover, foreign exchange controls inhibit depreciation of the real exchange rate, and thus slow or prevent reversal of the real exchange rate appreciation between 2004/05 and 2007/08, which has resulted in major price disincentives for exports and production of import substitutes. The modeling results presented here are not meant as definitive estimates, but rather as indicators of the broad magnitudes of the effect of the policies simulated. Further efforts are needed to refine the model simulations so as to include the effects of changes in world prices and to assess dynamic effects of shocks and policies on growth and income distribution. Nonetheless, the broad policy implications of this analysis are clear. There are substantial costs to both foreign exchange rationing and real exchange rate appreciation in terms of growth (reduced incentives for production of tradables) and income distribution (large rents accruing to the non-poor). Policy reforms need not involve full liberalization of the foreign exchange market, however. Various versions of managed floats and controls in foreign capital markets exist that can gradually reduce economic rents, improve incentives for exports and increase overall economic efficiency. Indeed, policies since late 2008 have effectively reduced the earlier appreciation of the real exchange rate. To recover more fully from the effects of the adverse external price and capital inflow shocks of 2007 and 2008, and to sustain the rapid propoor growth of recent years, though, further measures to restore real price incentives to exports, and reduce rents and economic inefficiencies arising from import rationing should be considered.